Gender Differences in Preferences for Flexible Work Hours: Experimental Evidence from an Online Freelancing Platform - Rakesh Banerjee; Tushar Bharati; Adnan Fakir; Yiwei Qian; Naveen Sunder (Institute of Labor Economics (IZA), 2024)
We conduct an experiment on a major international online freelancing labor market platform to study the impact of greater flexibility in choosing work hours within a day on female participation. We post identical job advertisements (for 320 jobs) covering a wide range of tasks (80 distinct tasks) that differ only in flexibility and the wage offered. Comparing the numbers of applicants for these jobs, we find that while both men and women prefer flexibility, the elasticity of response for women is twice that for the men. Flexible jobs receive 24 percent more female applications and 12 percent more male applications compared to inflexible jobs. Critically, these changes come at no cost to the quality of applications. In fact, we find suggestive evidence that flexible jobs attract higher quality female candidates. Our findings have important implications for explaining gender differences in labor market outcomes and for equity initiatives in firms.
Keywords: J22; O14; J16; L86; 330; workplace flexibility; online freelancing jobs; female labor force participation